Developing Job Satisfaction which Support Improvement of Organizational Performance Private High Schools Located in Indonesia - Haryani Hatta, Iha; Rini, Setia (International Journal of Engineering and Technology, 2018)
The objective of this research analysis leadership style, organizational culture, work motivation and competence, job satisfaction, andÂ organizational performance is to the perception senior high school teachers towards leadership style, organizational culture, work motivation, competence, job satisfaction andÂ organizational performance; identify the influence of leadership style, organizational culture, work motivation and competence partial towards job satisfaction and organizational performance; identify the influence of job satisfaction towards organizational performance. The respondents were 180 high school teachers from private schools in Jabodetabek (the Greater Jakarta Area), that were selected based on a multistage process, then analyzed with SEM, and using the Lisrel 8.5 program.Â The research results show that leadership style, organization culture, and work motivation influenced job satisfaction, however competence did not.Â Organization culture and competence affected the organizational performance, but leadership style and work motivation did not have influence on the organizational performance. The dominant path of effects showed that organizational culture affects job satisfaction and organizational performance.Â Â